Art vandalism - Cordess, Christopher (The British journal of criminology, 1993)
An account of a questionnaire study conducted by the authors to gather evidence about the present state of art vandalism in public art galleries in England, Scotland, and Wales is followed by a brief discussion of historical and contemporary accounts of destructive attacks on works of art. In this study a pattern of high prevalence of minor acts of destruction was reported, with a less frequent but substantial prevalence of major acts of destructiveness. The types of art works likely to be vandalized and some of the assumed psychological and psychiatric Characteristics of the perpetrators are discussed